Conventional and Microwave‐assisted Total Synthesis, Antioxidant Capacity, Biological Activity, and Molecular Docking Studies of New Hybrid Compounds. (25th August 2016) - Demirci, Serpil; Mermer, Arif; Ak, Gokhan; Aksakal, Fatma; Colak, Nesrin; Demirbas, Ahmet; Ayaz, Faik Ahmet; Demirbas, Neslihan
Abstract : Thiomorpholine was converted to the corresponding 1, 3, 4‐oxadiazole (4 ), arylidenehydrazide (5a, 5b, 5c, 5d, 5e ), and 1, 2, 4‐triazole (7a and, 7b ) derivatives via the formation of hydrazide (3 ). Compounds4 and7 were next converted to the corresponding Mannich bases containing piperidin, β‐lactam, fluoroquinolone, piperazine, or morpholine core. Conventional and microwave‐assisted methods were used for all syntheses. The effect of acid catalyst onMannich reactions was also investigated. All the newly synthesized compounds were screened for their antimicrobial, antiglucosidase, antilipase, anti‐urease, and antioxidant activities. Most exhibited good–moderate antibacterial and/or antifungal activity. Docking of some of the synthesized compounds into the active sites of lipase, α‐glucosidase, and urease was carried out in order to predict the binding affinities and noncovalent interactions stabilizing the enzyme–ligand complexes. Docking results complemented well the experimental results on inhibitory effects of compounds. Higher binding affinities were observed for active compounds in contrary to inactive ones. Abstract :